PENGARUH TINGKAT PEMBERIAN PAKAN BERBEDA TERHADAP LAJU PERTUMBUHAN IKAN NILEM (Osteochilus hasselti) YANG DIPELIHARA PADA SISTEM BIOFLOK RASIO C/N 20 - ahsan shiddiq robbani Ahsan; Fia Sri Mumpuni; Yudi Wahyudin (Universitas Djuanda, 2023)
Biofloc technology is an alternative in overcoming the problem of feed waste in hard-lipped barb culture media. The decline in hard-lipped barb production was caused by limited knowledge and traditional aquaculture. This research was conducted with the aim of knowing the effect of different feeding levels on the ratio of C/N 20 on the growth of hard-lipped barb (Osteochilus hasselti). This research was conducted in May 2021-June 2022 with a trial period of May-June 2021. The design used was a Completely Randomized Design with 3 treatments (feeding rate 1%, feeding rate 3%, feeding rate 5%) and 4 replications. Parameters observed included specific length growth rate (SLGR), specific weight growth rate (SWGR), feed efficiency (FE), and survival rate (SR). Water quality parameters (DO, temperature, Ammonia, CO2, and pH) were analyzed descriptively. The results showed that the different levels of feeding with a C/N ratio of 20 had a significant effect on SLGR, SWGR, FE, and SR. SLGR in the treatment of FR 1% (0.17±0.03), FR 3% (0.28±0.03), and FR 5% (0.32±0.01). SWGR in treatment A (0.33±0.06), B(0.95±0.04), and C(1.53±0.11), FE at 1% FR treatment (16.85±1, 12%), FR 3% (25.04±0.73%), and FR 5% (30.95±1.87%). SR in the treatment of FR 1% (55.83%), FR 3% (59.16%), and FR 5% (68.33%). FR 5% treatment had the highest growth rate compared to FR 1% and FR 3% treatment. The water quality during the 40-day trial period was still within normal limits for Nilem fish cultivation in the biofloc system.